Emotions and Experience of Fathers applying Kangaroo Care in the Eastern Anatolia Region of Turkey: A Qualitative Study - Gunay, Ulviye; Coskun Simsek, Didem (Sage Publications Inc, 2021)
The aim of this study was to investigate the emotions and experiences of fathers in Eastern Anatolia Region of Turkey who applied kangaroo care in the neonatal intensive care unit. This study applied the qualitative descriptive design. The study included 12 fathers at the NICU of a university hospital. The fathers practiced kangaroo care with their babies two times a day for 15 days. Content analysis was then conducted to determine the main themes and sub-themes of the interviews. Three main themes and six sub-themes emerged from the analysis: (1) Emotions of being a father (feeling that the baby belongs to own and feeling the warmth and scent of the baby); (2) Confidence in fathering roles (self-confidence and caring for the baby); and (3) Happiness in the new parent role (seeing the baby calm down, hugging the baby and touching the baby's skin).
Keywords: Kangaroo care; new-born; emotions; experience; fathers